Biological Activities of Iraqi Fig (Ficuscarica) CrudeEthanolic and Total Flavonoids Extracts - Al-Halbosiy, Mohammad Mahmoud Farhan; Hasan, Zainab Yaseen Mohammed; Mohammad, Farooq Ibrahem; Abdulhameed, Baraa Abdulhadi (Iraqi Journal of Science, 2020)
The present study focuses on the biological strategy for treating cancer and parasitic infections, such as leishmaniasis antiparasitic activity, forthe crude alcoholic extract ofFicus leaves and their extracted total flavonoids with a comparison between their effects.The flavonoids were extracted from the leaves of the mature Ficuscaricausing the reflux extraction method. Total flavonoids were detected qualitatively by TLC techniquewhich demonstratedthat the plant was rich indifferent flavonoids, especially Rutin, Quercetin, Kaempferol, luteolin and others. Quantitatively, the plant total flavonoids content was 337.3 mg / 100 g fig leaves calculated as rutin.The biologicaleffects of the crude and purified total flavonoid on cell lines (L-20B and MCF7) and two parasites (Leishmaniatropica ,Leishmaniadonvani) were investigated. Maximum growthinhibition rates forthe total flavonoids onthe cell linesL20B andMCF7 reached 43 % at the concentration of 0.169 mg/ml and 28% at the concentration of 2.7 mg/ml, respectively, in comparison with the negative control. The ethanoliccrude extract had a low effect on L20-B cell line, while the inhibition rate forMCF-7 cell linereached 34% at a concentration of 0.084 mg/ml. For Leishmaniatropica,the total flavonoid and crude plant extractcaused maximum inhibition rates of 48% and 56%, respectively,at a concentration of 2.7 mg/ml for both. Cytotoxicity valueon Leshmaniadonovani was 20% for the crude extract at 1.35 mg/ml concentration, whereas it was11% for the total flavonoids at a concentration of 0.169 mg/ml. In conclusion, the differences in anticancer and anti-parasitic activitiesareattributed to differentcompounds present in each extract.